2010
DOI: 10.1590/s1676-06032010000300004
|View full text |Cite
|
Sign up to set email alerts
|

The role of avian frugivores on germination and potential seed dispersal of the Brazilian Pepper Schinus terebinthifolius

Abstract: The role of avian frugivores on germination and potential seed dispersal of the Brazilian Pepper Schinus terebinthifolius. Biota Neotrop. 10(3): http:// www.biotaneotropica.org.br/v10n3/en/abstract?article+bn00910032010.Abstract: Frugivorous birds play a key role in seed dispersal and establishment of a range of plant species, including invasive weeds, such as the Brazilian Pepper Schinus terebinthifolius. The potential of seed dispersal of Schinus by birds with varied feeding behaviours was studied through se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…), diet specializations or foraging methods, since T. chiguanco swallows entire fruits, whereas T. bonariensis mandibulates fruits (D'Avila et al . ). In concordance with other studies, this finding suggests that effects of seed passage through avian guts are dependent on the interacting bird species (Robertson et al .…”
Section: Discussionmentioning
confidence: 97%
“…), diet specializations or foraging methods, since T. chiguanco swallows entire fruits, whereas T. bonariensis mandibulates fruits (D'Avila et al . ). In concordance with other studies, this finding suggests that effects of seed passage through avian guts are dependent on the interacting bird species (Robertson et al .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, it has been suggested that minor abrasion may facilitate germination success of ingested seeds, while excessive abrasion of seeds may reduce germination success (D'Avila et al 2010). Barnea et al (1991) reported that there are plant species that require seed coat abrasion for germination or that require only pulp removal for germination.…”
Section: Discussionmentioning
confidence: 99%
“…The process of seed dispersal by avian frugivores usually involves the consumption of pulp and regurgitation or excretion of intact seeds (D'Avila et al 2010;Fedriani et al 2011;Czarnecka et al 2012). This process is mutually beneficial as plants benefit from seed dispersal away from the parent plant to locations with fewer pathogens (Wenny 2001;Aslan 2011;Fricke et al 2013) while frugivores benefit from important food resources and energy rewards (Jordaan et al 2011b; Mokotjomela et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zonotrichia capensis (tico-tico) e Stephanophorus diadematus (cabeça-de-velho) foram as aves com a maior frequência de visitas e de registro de consumo efetivo dos frutos, sem a ocorrência de períodos preferencias para visitação. De maneira geral, as aves apresentam o comportamento de consumir os frutos sem destruir as sementes, mesmo com a passagem pelo trato digestório (Grelle & Garcia, 1999) que, por sua vez, pode interferir positivamente na germinação de sementes (D' Avila et al, 2010;Guerta et al, 2011). Aves são consideradas excelentes dispersoras pelo fato de depositarem suas fezes em locais distantes das plantas parentais, nos quais as taxas de predação e competição são menores (Francisco & Galetti, 2001).…”
Section: Discussionunclassified